2018
DOI: 10.1177/0954411918790286
|View full text |Cite
|
Sign up to set email alerts
|

An engineering approach towards a more discrete and efficient urinary drainage system

Abstract: Modern urinary catheter-to-leg-bag systems suffer from a number of shortcomings. Drainage tubing of current urinary leg bags is perceived as unnecessarily bulky compared to the indwelling catheters to which it is connected, and catheter designs are prone to the formation of biofilms, leading ultimately to encrustation and blocking. We used analytical and experimental engineering methodologies, aligned with current international (International Standards Organisation) and European standards, to optimise drainage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The model could also be modified to enable investigation of the flow performance of other endourological devices, such as sphincter stents or urethral catheters, which are also known to suffer from encrustation, particularly upon long-term deployment. 42,43 Previous studies have demonstrated a qualitative dependence of encrustation on the flow field within a urethral catheter; 44 a more quantitative investigation could, thus, be performed in future research. Numerical models could also be further developed to include simulation of particle dynamics in urological devices.…”
Section: Discussionmentioning
confidence: 99%
“…The model could also be modified to enable investigation of the flow performance of other endourological devices, such as sphincter stents or urethral catheters, which are also known to suffer from encrustation, particularly upon long-term deployment. 42,43 Previous studies have demonstrated a qualitative dependence of encrustation on the flow field within a urethral catheter; 44 a more quantitative investigation could, thus, be performed in future research. Numerical models could also be further developed to include simulation of particle dynamics in urological devices.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In human paediatric patients, catheters with a diameter smaller than 10 Fr and with an insertion length of more than 10 cm are at risk for spontaneous knotting. 11 Urethral catheters wider than 10 Fr are only used in large breed dogs; thus, smaller veterinary patients, such as paediatric patients, may be prone to urethral catheter knotting. 5 Interestingly, Singh and Sinha published a case series and literature review noting that most human patients presenting with a retained catheter are paediatric patients (97% were children, n = 31).…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate drainage effectiveness due to kinking of these tubes is described in 14% of cases (2/14 tubes) [ 8 ]. A possible cause could be the thin wall (0.4 mm) in relation to the large inner diameter (1.2 mm) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tube used in this study is constructed for wound drainage with suction, therefore it has a relatively thick wall (0.5 mm). The thick wall (0.5 mm) in relation to the small inner diameter (1 mm) could result in high kink resistance [ 14 ]. Nevertheless, due to its multiple fenestration (20 side holes), the tube has a very good drainage performance, which also reduces the risk of blockage.…”
Section: Discussionmentioning
confidence: 99%